Adjunctive radiograph diagnostic in vertical mandibular asymmetry - Kirubanandan Sathya Moorthy; Ervina Sofyanti; Trelia Boel; Jesslyn Okto Govanny; Aditya Rachmawati (Dental Journal (Majalah Kedokteran Gigi), 2021)
Background: The development of radio diagnostics in orthodontics is still a challenge in treating skeletal anomaly with facial asymmetry. The assessment of skeletal symmetry, which can be obtained by frontal radiographs such as panoramic radiograph and posteroanterior cephalograph, is still limited. Purpose: The aim of this study is to evaluate panoramic radiograph and posteroanterior cephalograph in measuring the vertical mandibular asymmetry based on Kjellberg technique. Methods: This study was a cross-sectional study of 43 pre-treatment panoramic radiographs and posteroanterior cephalographs from dental faculty students at Universitas Sumatera Utara between 18–25 years old. The subjects have fully erupted permanent teeth until the second molar and complained about facial asymmetry. The validity and reliability of vertical mandibular asymmetry of Kjellberg technique with Cliniview software in both radiographs used Cohen-K analysis. Results: The measurement of vertical mandibular asymmetry showed no significant differences using panoramic radiograph and posteroanterior cephalograph (0.073-0.321 > 0.05). Conclusion: The vertical mandibular asymmetry analysis with Kjellberg technique in panoramic radiograph is potent as an adjunctive diagnostic tool in vertical mandibular asymmetry.